Unholy messenger : the life and crimes of the BTK serial killer - Singular, Stephen (New York : Scribner, 2006)
To all appearances, Dennis Rader was a model citizen in the small town where he had lived with his family almost his entire life. He was a town compliance officer, a former Boy Scout leader, the president of his church congregation, and a seemingly ordinary father and husband. But Rader$1 (Bs average life belied the existence of his other self: he was the BTK serial killer. The self-named BTK (for Bind, Torture, Kill) had terrorized Wichita for thirty-one years, not only with his brutal, sexually motivated crimes, but also through his taunting communications with the media and law enforcement. Drawing from extensive interviews with Rader$1 (Bs pastor, congregation, detectives, and psychologists, and from his unnervingly detailed thirty-two-hour confession, author Singular explores the chilling story of a man considered a "spiritual leader" by his pastor and congregation, who turned out to be the devil next door.--From publisher description.s
"A Lisa Drew book."
Keywords: Rader, Dennis, -- 1945-; Serial murders -- Kansas -- Wichita -- Case studies; Serial murderers -- Kansas -- Wichita -- Biography; Serial murder investigation -- Kansas -- Wichita